Recent developments on nanocomposites based on spinel ferrite and carbon nanotubes for applications in electromagnetic interference shielding and microwave absorption - Yadav, Raghvendra Singh; Kuřitka, Ivo (Critical reviews in solid state and materials sciences, 2024)
Several carbon nanotubes and spinel ferrite-based nanocomposites have been created in recent years and are considered to be viable options for an effective electromagnetic interference (EMI) shielding and microwave absorber material. The current development of carbon nanotube and spinel ferrite-based nanocomposites for EMI shielding and microwave absorption is the topic of this study. The fundamental mechanism of EMI shielding and microwave absorption is described. The EMI shielding and microwave absorption properties of carbon nanotubes and spinel ferrite, as well as their numerous components such as graphene, MXene, semiconductor nanoparticles, polymer, rubber, and so on, are thoroughly examined. This paper also discusses potential problems and solutions for creating new nanocomposites for the next generation of shielding applications.